Geochemical analyses suggest stratigraphic origin and late Miocene age of reworked vertebrate remains from Penanjong Beach in Brunei Darussalam (Borneo). (2nd November 2021) - Kocsis, László; Botfalvai, Gábor; Qamarina, Qahirah; Razak, Hazirah; Király, Edit; Lugli, Federico; Wings, Oliver; Lambertz, Markus; Raven, Han; Briguglio, Antonino; Rabi, Márton
ABSTRACT: We report on sporadic fossil vertebrates from Brunei Darussalam (Borneo). Most of these isolated remains are reworked and derive from Penanjong Beach known for former coastal cliffs used to be rich in marine molluscs. Previously, the only vertebrate remains reported were shark teeth. With new material, the fish fauna is now represented by six shark and a single ray taxa, while remains of three turtle families were discovered (Trionychidae, Cheloniidae, Geoemydidae). This fauna is compared to nearby upper Miocene fossiliferous beds from where remains of cheloniid and trionychid turtles were unearthed. To assess the origin of the reworked remains, rare earth element (REE) concentrations of the fossil bioapatite were compared between the reworked and the geographically closest in-situ Ambug Hill fauna. The obtained trend in REE variations are identical, revealing similar REE uptake mechanism and early diagenetic conditions. With the additional fact that the succession outcropping at Ambug Hill cuts the coastline imply that the majority of the reworked fossils derive from the local Miocene beds. This is supported by Sr-isotope ages from reworked calcite bivalve shells ranging from 9.74 to 6.62 Ma. These turtle remains thus represent the hitherto known first Neogene fossil tetrapods from Borneo.